E-DAKWAH DALAM PESANTREN VIRTUAL - Akhmad Rifa’i (Millah: Journal of Religious Studies, 2009)
The research aims to recognize, inform and to simplify the management of dakwah  in the cyber or virtual media. The result of the study may support and provide inspiration of  Muslim society to develop and create an innovative dakwah in virtual media. The primary data are obtained from the Virtual Pesantren. The data concern with the management of  the Virtual Pesantren concerning its service on religious information  that is interesting and that contains educational programs. To analyze the data, the study uses qualitative-descriptive technique and the commentary of  the data is in the form of narrative reports. The finding shows that the creativity of Islamic students or management in carrying out the Virtual Pesantren is very innovative and high performance. Infact, many users who visit or attend as members o f  the Virtual Pesantren prove these findings. Moreover, the virtual Pesantren becomes a service agent on religious information that is open for  all societies and religions.